2019
DOI: 10.1101/534297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reevaluating the Fusobacterium Virulence Factor Landscape

Abstract: Fusobacterium are Gram-negative, anaerobic, opportunistic pathogens involved in multiple diseases, including the oral pathogen Fusobacterium nucleatum being linked to the progression and severity of colorectal cancer. The global identification of virulence factors in Fusobacterium has been greatly hindered by a lack of properly assembled and annotated genomes. Using newly completed genomes from nine strains and seven species of Fusobacterium , we report the identification and correction of virulence factors fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
1
0
1
Order By: Relevance
“…For example, Umana et al demonstrated that F. necrophorum subsp. funduliforme showed better adherence to HCT116 cells than F. nucleatum, despite the fact that the former has far fewer TVa adhesins, but instead possess more TVc adhesins than F. nucleatum [65]. It is highly likely that factors other than the TVa adhesins contribute to variability in adhesion, and reverse genetic approaches will be required to elucidate the function of novel adhesins.…”
Section: Analysis Of Adhesion Phenotypesmentioning
confidence: 99%
“…For example, Umana et al demonstrated that F. necrophorum subsp. funduliforme showed better adherence to HCT116 cells than F. nucleatum, despite the fact that the former has far fewer TVa adhesins, but instead possess more TVc adhesins than F. nucleatum [65]. It is highly likely that factors other than the TVa adhesins contribute to variability in adhesion, and reverse genetic approaches will be required to elucidate the function of novel adhesins.…”
Section: Analysis Of Adhesion Phenotypesmentioning
confidence: 99%
“…Urutan lengkap nukleotida dari leukotoxin F. necrophorum telah berhasil diidentifikasi. Protein leukotoxin F. necrophorum disandi oleh operon trisistronik yang terdiri dari lktB, A, dan C (Umana et al, 2019). Protein lktA telah diidentifikasi mampu menginduksi apoptosis dan nekrosis pada leukosit sapi (Pillai et al, 2021;Tadepalli, Stewart, Nagaraja, & Narayanan, 2008).…”
Section: Pendahuluanunclassified